Exercise‐induced bronchospasm related to different phenotypes of rhinitis without asthma in primary schoolchildren: the French Six Cities Study. Issue 6 (June 2014) - Caillaud, D.; Horo, K.; Baiz, N.; Banerjee, S.; Charpin, D.; Lavaud, F.; de Blay, F.; Raherison, C.; Annesi‐Maesano, I.
Summary Background Exercise‐induced bronchospasm (EIB) is frequent among asthmatic children. However, opinions differ on the relation between EIB and rhinitis in the absence of asthma. Objectives We assessed the relationship between EIB and various phenotypes of rhinitis according to asthmatic status at the general population level in the Six Cities Study. Methods Of 7781 schoolchildren with a mean age of 10 years underwent an EIB test and skin prick test to assess allergic sensitization. Their parents completed a standardized questionnaire recording asthma‐like symptoms and past‐year rhinoconjunctivitis, ever hay fever (EHF), and a score for allergic rhinitis (SFAR) ≥7 as a marker of 'past‐year allergic rhinitis'. Exercise‐induced bronchospasm was defined as a fall in peak expiratory flow rate ≥15% after exercise. Results Of the 6813 schoolchildren retained for analysis, 227 (3.33%) experienced EIB after exercise. Odds ratios [95% confidence intervals] between EIB and allergic rhinitis phenotypes in the absence of asthma were 1.56 [0.92–2.63] for EHF, 1.97 [1.16–3.35] for past‐year rhinoconjunctivitis, and 1.84 [1.16–2.91] for a SFAR ≥7. Results were unchanged after adjustment for confounders. Multiple correspondence analysis showed that EIB, although related to asthma, constitutes a separate entity. Exercise‐induced bronchospasm was not significantly related to familial history of asthma. Conclusion In our large population‐based sample of children, different phenotypes of atopic rhinitis were associated with EIB, independently of asthma. Exercise‐induced bronchospasm, although related to asthma, seems to constitute a separate entity. Clinical relevance In this large (6813) sample of 10‐year children drawn from the general population, EIB is associated with rhinitis phenotypes in the absence of asthma. Furthermore, it constitutes an entity independent from asthma and is not related to a familial history of asthma. Thus, investigating these symptoms could be important in this disease, as a specific nasal treatment might improve EIB in these children.